2019
DOI: 10.3390/nu11112773
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Inflammation and Leptin Resistance by Pyrogallol-Phloroglucinol-6,6-Bieckol on in the Brain of Obese Animal Models

Abstract: Obesity induces inflammation both in the adipose tissue and the brain. Activated macrophage infiltration, polarization of macrophages to a more inflammatory type (M1), and increased levels of pro-inflammatory cytokines are related to brain inflammation, which induces leptin resistance in the brain. Pyrogallol-phloroglucinol-6,6-bieckol (PPB), a compound from Ecklonia cava, has anti-inflammatory effects. In this study, we evaluated the effects of PPB effect M1 polarization and inflammation and its ability to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…Decreased ObR protein and mRNA expression and localization on adipocyte surfaces are key determinants of cell sensitivity to leptin [15]. Interestingly, PPB also restored leptin sensitivity in HFD-induced obese mice and ob/ob mice [55]. We also found that ECE inhibited HFD-induced decreases in ObR expression, which suggests that ECE enhanced adipocyte leptin sensitivity by maintaining ObR expression ( Figures 5(f )-5(h)).…”
Section: Effects Of E Cava Extract On Serum Leptin and Adiponectin Lmentioning
confidence: 51%
“…Decreased ObR protein and mRNA expression and localization on adipocyte surfaces are key determinants of cell sensitivity to leptin [15]. Interestingly, PPB also restored leptin sensitivity in HFD-induced obese mice and ob/ob mice [55]. We also found that ECE inhibited HFD-induced decreases in ObR expression, which suggests that ECE enhanced adipocyte leptin sensitivity by maintaining ObR expression ( Figures 5(f )-5(h)).…”
Section: Effects Of E Cava Extract On Serum Leptin and Adiponectin Lmentioning
confidence: 51%
“…Polyphenols were demonstrated to be very well capable of suppressing the increase of TLRs, including TLR4 [ 124 , 126 , 127 ], TLR2 [ 124 , 127 ] and TLR7 [ 124 ]. TLRs as primary sensors of microbial products activate signaling pathways that lead to the induction of immune- and inflammatory genes, such as the NF-κB pathway.…”
Section: Phenolic Compounds and Phytosterolsmentioning
confidence: 99%
“…In line with these observations, elevated TNF-α levels lead to a decrease in Azgp1 mRNA and protein levels in adipose tissues of ob/ob mice [ 177 , 192 ]. Additionally, IL-6, TNF-α [ 195 , 196 , 197 ], IL-1β, IL-10 [ 193 ] and plasminogen activator inhibitor-1 (PAI-1) are increased in the adipose tissue and the spleen of ob/ob mice [ 195 , 197 ]. IFN-γ expression decreases in ob/ob mice [ 193 ] and other studies have reported lower adiponectin values in the adipose tissue and in the spleen [ 193 , 195 ].…”
Section: Diet Inflammation and Gut Microbiota In T2dm Modelsmentioning
confidence: 99%
“…Moreover, LPS levels are higher in plasma from ob/ob mice [ 198 ] and in C57BL/6NTac mice on HFD [ 174 ]. Additionally, NF-kB levels are elevated in the brain of ob/ob mice [ 196 ]. Other markers, such as CD11 and CD86 are increased in the brain and visceral fat tissue, whereas the expression of CD206 decreases [ 196 , 197 ].…”
Section: Diet Inflammation and Gut Microbiota In T2dm Modelsmentioning
confidence: 99%
See 1 more Smart Citation